Methodology put to work - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
After extensive preparation, the methodology for national stakeholders to establish their priority agricultural information themes is now nearing the application phase.The methodology, which aims at strengthening capacities in the formulation,...